2015
DOI: 10.1186/s12862-015-0373-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of peroxisome proliferator-activated receptor alpha to hibernation in bats

Abstract: BackgroundHibernation is a survival mechanism in the winter for some animals. Fat preserved instead of glucose produced is the primary fuel during winter hibernation of mammals. Many genes involved in lipid metabolism are regulated by the peroxisome proliferator-activated receptor alpha (PPARα). The role of PPARα in hibernation of mammals remains largely unknown. Using a multidisciplinary approach, we investigated whether PPARα is adapted to hibernation in bats.ResultsEvolutionary analyses revealed that the ω … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…4e, the levels of ATF4 were found to be increased during torpor. These findings suggest that the PERK/ EIF2/ATF4 signal transduction pathway is activated in torpid bats and that these bats selectively produce some proteins to cope with endoplasmic reticulum stress as seen in many hibernating mammals 51,52 . Since the levels of several UPR ER makers, such as ATF4, PERK, and GRP78, are increased in various tissues (e.g., brain, liver, and muscle) of different mammalian species (e.g., ground squirrels, hamsters, and bats) during hibernation 26,29,[53][54][55] , these findings also support our hypothesis that UPR ER is a common stress response in bats.…”
Section: Discussionmentioning
confidence: 87%
“…4e, the levels of ATF4 were found to be increased during torpor. These findings suggest that the PERK/ EIF2/ATF4 signal transduction pathway is activated in torpid bats and that these bats selectively produce some proteins to cope with endoplasmic reticulum stress as seen in many hibernating mammals 51,52 . Since the levels of several UPR ER makers, such as ATF4, PERK, and GRP78, are increased in various tissues (e.g., brain, liver, and muscle) of different mammalian species (e.g., ground squirrels, hamsters, and bats) during hibernation 26,29,[53][54][55] , these findings also support our hypothesis that UPR ER is a common stress response in bats.…”
Section: Discussionmentioning
confidence: 87%
“…Indeed, NFYA, a known regulator of HSP 70/90 and a TF expressed higher in bats (Fig. 4d ), has also been implicated in torpor (Han et al 2015 ). Other additional elements compared to human included GATA, NFAT, ELK1/Ets and MYB binding sites, though these had lower binding scores.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of transcriptomes in small hibernating mammals have revealed that many genes involved in metabolism are differentially expressed during hibernation. Specifically, the genes involved in carbohydrate catabolism are downregulated during hibernation, while genes responsible for lipid catabolism are upregulated (Carey et al, 2013; Stevenson et al, 2014; Han et al, 2015; Xiao et al, 2015; Sommer et al, 2016). We also found that the relative abundance of functional categories associated with amino acid metabolism increased in the early winter compared with the late summer, consistent with other studies showing that hibernating bats have elevated levels of amino acid metabolism during hibernation (Pan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%